2007
DOI: 10.1051/cocv:2007031
|View full text |Cite
|
Sign up to set email alerts
|

Local null controllability of a two-dimensional fluid-structure interaction problem

Abstract: Abstract.In this paper, we prove a controllability result for a fluid-structure interaction problem.In dimension two, a rigid structure moves into an incompressible fluid governed by Navier-Stokes equations. The control acts on a fixed subset of the fluid domain. We prove that, for small initial data, this system is null controllable, that is, for a given T > 0, the system can be driven at rest and the structure to its reference configuration at time T . To show this result, we first consider a linearized syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 19 publications
(21 reference statements)
1
45
0
Order By: Relevance
“…The results on semi-linear equations have been extended to the case of non smooth coefficients [DOP02,BDL07a,Le 07,LR10b]. The use of global parabolic Carleman estimates has also allowed to address the controllability of non linear equations such as the Navier-Stokes equations [Ima01,FCGIP04], the Boussinesq system [FCGIP06], fluid structure systems [IT07,BO08], weakly coupled parabolic systems [de 00, ABDK05, ABD06, GBPG06] to cite a few. A review of the application of global parabolic Carleman estimates can be found in [FCG06].…”
Section: Introductionmentioning
confidence: 99%
“…The results on semi-linear equations have been extended to the case of non smooth coefficients [DOP02,BDL07a,Le 07,LR10b]. The use of global parabolic Carleman estimates has also allowed to address the controllability of non linear equations such as the Navier-Stokes equations [Ima01,FCGIP04], the Boussinesq system [FCGIP06], fluid structure systems [IT07,BO08], weakly coupled parabolic systems [de 00, ABDK05, ABD06, GBPG06] to cite a few. A review of the application of global parabolic Carleman estimates can be found in [FCG06].…”
Section: Introductionmentioning
confidence: 99%
“…V S ≡ 0, this condition is trivially satisfied for all σ > 0. Let us also note that in dimension 2 or 3, for a rigid body immersed into a viscous incompressible fluid (and for a fluid domain that is connected), this problem disappear both for the controllability problem (see [20], [6], [5]) and for the stabilization problem (work in progress).…”
Section: Mḧ(t) = [Vx](t H(t))mentioning
confidence: 99%
“…In Section 2 we first discuss the existence of solutions for (4) and on condition (6). In Section 3, we construct a change of variables to reduce the problem (1)- (3) to a cylindrical domain.…”
mentioning
confidence: 99%
“…Very recently Imanuvilov and Takahashi [12] and Boulakia and Osses [1] have studied the null controllability, locally about zero, of a system coupling the Navier-Stokes equations with the motion of a rigid body. Their analysis is based on Carleman estimates for a linearized system.…”
Section: Introductionmentioning
confidence: 99%
“…In the system coupling the Navier-Stokes equations with a rigid body, the domain occupied by the fluid depends on the position of the solid and therefore depends on the time variable. The linearized system may be stated either in a time dependent domain as in [1] or in a fixed domain as in [12]. In the present paper, we are going to establish Carleman inequalities for a linearized fluid-solid structure model, stated in a fixed domain Ω.…”
Section: Introductionmentioning
confidence: 99%